"Unpersonen" : wer waren sie wirklich? ; Bucharin, Rykow, Trotzki, Sinowjew, Kamenew - Heitkam, Barbara; Bucharin, Nikolaj Ivanovič 1888-1938; Bucharin, Nikolaj Ivanovič 1888-1938 BeteiligteR; Rykov, Aleksej I. 1881-1938 BeteiligteR; Trockij, Lev Davidovič 1879-1940 BeteiligteR; Zinovʹev, Grigorij Evseevič 1883-1936 BeteiligteR; Kamenev, Lev Borisovič 1883-1936 BeteiligteR (Dietz Verl, 1990)
Nikolai Bucharin ; Alexeyj Rykow ; Leo Trotzki ; Grigori Sinowjew ; Lew Kamenew